A STUDY ON THE FREQUENCY OF ANTI-TUBERCULOUS THERAPY INDUCED HEPATITIS (Journal of Medical & Health Sciences Review, 2025)
Objective: The aim of this study was to determine the frequency of anti-tuberculous therapy (ATT) induced hepatitis.Methodology: The design of this study was a descriptive study. This study was conducted at DHQ Hospital Mirpur, and duration of this study was from May 2024 to December 2024. In this study the cases of known Tuberculosis were included. Anti-Tuberculosis Therapy included Isoniazid, Rifampicin Ethambutol and Pyrazinamide according to standard WHO recommended doses. The cases suffering from hepatitis B, C or HIV or those with derange liver functions were excluded from this study. The cases were followed weekly and Liver function tests (LFTs) were performed and hepatitis was labelled as yes where there was rise in liver enzymes three times upper limit with symptoms (nausea/vomiting/abdominal pain) or 5 times without any symptoms. The final outcome was seen at 4 weeks.Results: In this study there were total 100 cases of TB out of which 70 (70%) were males and 30 (30%) females. The mean age of the subjects was 38.11± 11.45 years. There were 78 cases with pulmonary and 22 had EPTB. ATT induced hepatitis was observed in 6 (6%) of the cases. ATT induced hepatitis was significantly high in males affecting 5 (7.14%) cases with p value of 0.04. There was no significant difference in terms of weight groups with p= 0.68. Hepatotoxicity was more seen in cases having EPTB where 2 out of 22 cases had it; although this difference was statistically not significant with p=0.13.Conclusion: ATT induced hepatitis is uncommon but is seen significantly high in male gender.